2018
DOI: 10.1136/bmj.k4383
|View full text |Cite|
|
Sign up to set email alerts
|

Reporting harms more transparently in trials of cancer drugs

Abstract: Studies of cancer drugs often use terms that downplay the seriousness of adverse events. Bishal Gyawali and colleagues call for greater clarity and transparency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
1
22
1
Order By: Relevance
“…Finally, our assessments focused on the primary endpoints of randomised controlled trials; it remains possible that results for other outcomes could be at lower risk of bias. However, this is unlikely because pervasive limitations are well documented for secondary endpoints of cancer drug trials, including harms979899 and quality of life outcomes 100101. Therefore, we might not have fully captured other important shortcomings of randomised controlled trials that support cancer drug approvals.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our assessments focused on the primary endpoints of randomised controlled trials; it remains possible that results for other outcomes could be at lower risk of bias. However, this is unlikely because pervasive limitations are well documented for secondary endpoints of cancer drug trials, including harms979899 and quality of life outcomes 100101. Therefore, we might not have fully captured other important shortcomings of randomised controlled trials that support cancer drug approvals.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative 'before and after' data on pulmonary function were not given in any of observational studies(2) which is consistent with the under-reporting of harms that has been found to be a feature of cancer trials. (24) The overriding limitation of this study is its small size with only 65 participants.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic low-grade toxicities may be even more important affecting HRQoL for this group of patients [19]. In addition, recently published papers [18,20] elucidated that publications reporting the effectiveness and safety of cancer drugs often use subjective terms that downplay the seriousness of adverse events. A representative example is the SOLO2 trial, where olaparib did not improve the prespecified primary quality-of-life analysis, and this was interpreted as 'olaparib is not having a significant detrimental effect on QoL' and 'there were clinically meaningful patient-centred benefits despite the adverse effects' [18].…”
Section: Discussionmentioning
confidence: 99%